Effect of Relining Methods on Dimensional Accuracy and Stability of Conventional Complete Dentures - A Literature Review (Medical Forum Monthly, 2024)
Objective: To review the literature in order to evaluate the effect of relining methods on dimension accuracy and stability of conventional complete denture.Study Design: Review of literature.Materials and Methods: The literature search was mainly performed through internet. Abstracts and full text of articles published in journals indexed by index Medicus were searched Pubmed. A Google search was also performed to obtain material available at websites of different dental associations. The comparison was made among original research studies, cross sectional surveys, meta analysis, review articles and guidelines in context to the purpose of study.Results: The laboratory reline method has relatively good dimensional stability and strength, but presents a major drawback i.e patient has to be without denture for a certain period of time, on the other hand chairside reline method seems to be convenient and easy and require short working time. Autopolymerising acrylic resins have the potential of causing chemical or thermal burns of the oral mucosa. Autopolymerising direct chairside relining materials have been used widely in clinical setting.Conclusion: The Direct chairside method is advisable as it presents the least gap at posterior palatal seal area. However chairside relines are technique sensitive and require experience.